Pajak Penghasilan Atas Usaha Apotek Waralaba di Kabupaten Klaten - Suparna wijaya; Cindy Septyanasari (STIE Jambatan Bulan, 2021)
With the COVID-19 pandemic, businesses related to health are increasing, one of which is pharmacies. The purpose of this study is to explain the potential income tax on franchised pharmacy businesses and the barriers to taxation. The method used in this research is descriptive qualitative. The results show that the potential income tax on franchised pharmacies from the franchisee is Article 21, 23, 25 and 4 paragraph (2) of the Income Tax Act. The obstacles faced by franchisees in fulfilling their tax rights and obligations are related to frequent miscalculations.